2016
DOI: 10.1016/j.jaad.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of atopic dermatitis (AD): A systematic review and meta-analysis

Abstract: Background-Previous studies found conflicting results about whether childhood atopic dermatitis (AD) persists into adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
2
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(190 citation statements)
references
References 42 publications
9
156
2
8
Order By: Relevance
“…J. Kim и соавт. [4], обобщив резуль-таты 45 исследований, в которых участвовало более 110 тыс. пациентов из 15 стран, показали, что у детей старше 8 лет в 80% случаев уже отсутствовали симпто-мы атопического дерматита, и лишь менее чем у 5% признаки болезни сохранялись через 20 лет наблюде-ния.…”
Section: распространенностьunclassified
See 1 more Smart Citation
“…J. Kim и соавт. [4], обобщив резуль-таты 45 исследований, в которых участвовало более 110 тыс. пациентов из 15 стран, показали, что у детей старше 8 лет в 80% случаев уже отсутствовали симпто-мы атопического дерматита, и лишь менее чем у 5% признаки болезни сохранялись через 20 лет наблюде-ния.…”
Section: распространенностьunclassified
“…пациентов из 15 стран, показали, что у детей старше 8 лет в 80% случаев уже отсутствовали симпто-мы атопического дерматита, и лишь менее чем у 5% признаки болезни сохранялись через 20 лет наблюде-ния. Вместе с тем у детей с дебютом атопического дер-матита до двухлетнего возраста отмечен более низкий риск хронизации дерматоза в отличие от пациентов, Обмен опытом у которых первые патологические проявления возникли в более старшем возрасте [4].…”
Section: распространенностьunclassified
“…However, predicting which individuals will have persistent disease has not been possible. In a recently published metaanalysis of 45 studies from 15 countries (involving 110,651 patients, for a total of 434,992 patient-years), Kim and colleagues 14 found that three main factors were involved in the risk for persistence of AD into adulthood: (1) disease in childhood that persists for 10 years or more (compared to ≤5 years); (2) onset of AD later than 2 years of age; and (3) greater vs less severity of AD in childhood.…”
Section: Modulating Barrier Dysfunction In Admentioning
confidence: 99%
“…10 Atopic dermatitis is more frequent in childhood, especially in the first five years of life. 11,12 The prevalence or incidence of AD in the first five years of childhood is 10%-16.5% and is generally considered to be increasing worldwide, at least from the 1980s to early 2000s. [13][14][15] Most pediatric AD cases are mild-to-moderate in severity, with 84% of cases considered mild, 14% moderate, and only 2%…”
Section: Introductionmentioning
confidence: 99%
“…11 Children with moderate-to-severe AD at age 9-16 months are more likely to have persistent AD 6-12 years later compared to those with mild disease. 24 Fifty percent of subjects have at least one six-month symptom-/treatment-free period, but symptoms frequently recur until 20 years of age.…”
mentioning
confidence: 99%